Forearm Position Influences Triceps Brachii Activation During Triceps Push-Down Exercise - Marina Mello Villalba; Rafael Akira Fujita; Claudinei Iossi Junior; Matheus Machado Gomes (International Universities Strength and Conditioning Association, 2024)
Introduction: This study investigated the influence of forearm position (supinated or pronated) on the EMG activity of the triceps brachii lateralis head (TLA), triceps brachii longus head (TLO), flexor carpi radialis (FR), and extensor carpi radialis (ER) muscles during the triceps push-down exercise. Also, we analyzed the effect of different grips (handle vs standard padded pulley strap) to verify EMG activity of these muscles. Methods: Twenty-two adults participated in this study. They performed the single-arm triceps push-down exercise in four conditions: pronated forearm with handle (PRON-H), supinated forearm with handle (SUP-H), pronated forearm with standard padded pulley strap (PRON-S), and supinated forearm with standard padded pulley strap (SUP-S). Surface electrodes were placed over the TLA, TLO, FR, and ER on the dominant side. Results: The TLO showed higher EMG activity for SUP-H compared to all other conditions (p<0.001). Also, the FR EMG activity was higher with PRON-H condition (p<0.001), while the ER EMG activity was higher with SUP-H condition (p<0.001). Regarding the number of repetitions, participants performed fewer repetitions in the SUP-H condition compared to the PRON-H (p<0.001). Conclusion: Our study suggests that the position of the forearm during the triceps push-down exercise has a significant impact on the recruitment of specific muscles and overall exercise performance.